The role of Gingko biloba extract on autophagy modulation, protein clearance and neuronal cell death in an in vitro model of Alzheimer's disease - Khoza, Akile (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.